2020
DOI: 10.2217/epi-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Nonsyndromic Orofacial Clefts in Chile: LINE-1 Methylation and MTHFR Variants

Abstract: Aim: To evaluate the risk of nonsyndromic orofacial clefts (NSOFCs) associated with LINE-1 methylation, as a marker of global DNA methylation, and the effect of MTHFR functional variants on this variable. Patients & methods: LINE-1 methylation was evaluated by bisulfite modification coupled to DNA pyrosequencing in 95 NSOFC cases and 95 controls. In these subjects, MTHFR genotypes for variants c.C677T (rs1801133) and c.A1298C (rs1801131) were obtained. Results: Middle levels (second tertile) of LINE-1 meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Development of the lip and palate requires a complex series of events including formation of the upper lip and the primary palate and the division of the oronasal space, and any disturbance in this process may lead to NSCLP (Mossey, Little, Munger, Dixon, & Shaw, 2009 ). Previous studies have suggested that differential DNA methylation in several genes was associated with NSCLP (Cáceres‐Rojas et al, 2020 ; Y. Li et al, 2019 ; Xu et al, 2019 ; Yang et al, 2021 ). However, whole blood samples were used for most studies, and even if tissue samples were used a very few number of studies, their controls were not self‐control.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Development of the lip and palate requires a complex series of events including formation of the upper lip and the primary palate and the division of the oronasal space, and any disturbance in this process may lead to NSCLP (Mossey, Little, Munger, Dixon, & Shaw, 2009 ). Previous studies have suggested that differential DNA methylation in several genes was associated with NSCLP (Cáceres‐Rojas et al, 2020 ; Y. Li et al, 2019 ; Xu et al, 2019 ; Yang et al, 2021 ). However, whole blood samples were used for most studies, and even if tissue samples were used a very few number of studies, their controls were not self‐control.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have indicated that DNA methylation plays an essential role in the occurrence and development of diseases (Corso‐Díaz, Jaeger, Chaitankar, & Swaroop, 2018 ; Greenberg & Bourc'his, 2019 ; Weinberg et al, 2019 ). Although changes in the DNA methylation of few susceptible genes have been found in patients with CLP (Alvizi et al, 2017 ; Cáceres‐Rojas et al, 2020 ; Khan et al, 2019 ; Y. Li et al, 2019 ; Murthy, Gurramkonda, Karthik, & Lakkakula, 2014 ), the function of DNA methylation in CLP, especially in NSCLP remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Long interspersed nucleotide element‐1 (LINE‐1) is a marker of global DNA methylation. Studies have reported differential global DNA methylation patterns between NSOFC and controls using the methylation levels of LINE‐1 (Cáceres‐Rojas et al, 2020; Khan et al, 2018, 2019; Li et al, 2019). There is evidence to suggest that genetic variations (c.C677T and c.A1298C) in the MTHFR gene lead to low DNA methylation levels (Frosst et al, 1995; van der Put et al, 1998).…”
Section: Epigeneticsmentioning
confidence: 99%